(untitled) (Journal of Electrical, Electronics and Informatics, 2026)
Bali is among other provinces in Indonesia that experiences rapid development, particularly in the tourism sector, the creative industries, and the overall economy. This growth has driven an increasing demand for electricity across various sectors, including residential, industrial, and commercial sectors, as well as public services. To address this issue, electricity demand forecasting in Bali was carried out using an econometric approach for a period of 2025–2033. The projection result then is compared with that stated in the Electricity Supply Business Plan (RUPTL). The findings indicated that, using the proposed method, for an annual economic growth rate of 5.86%, the average annual growth rate of electricity demand is about 7.1%. In comparison, the RUPTL scenario stated that with an average annual economic growth rate of 7.0%, the average annual growth rate of electricity demand is about 7.0%. These results highlight the importance of the applied method in forecasting electricity demand, which are most affected by the economic growth within the region.